The Influence of Principal Leadership in the Implementation of Dual Track Program Innovation at SMA Budi Utomo Perak and SMA Negeri 8 Surabaya - Putri, Intan Zulfa Atarria; Rifqi, Ainur; Sholeh, Muhamad; Khamidi, Amrozi; Purwoko, Budi; Roesminingsih, Erny (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the leadership role of school principals in improving the quality of education, school management, and student competencies through various approaches, including Dual Track programs and educational innovation. This study reviewed the literature related to educational leadership, curriculum management, interpersonal communication, and student skill development at the high school level and emphasized strategies to improve the quality of teachers and students. The results of the study show that effective leadership, accompanied by strategic management and the implementation of innovative programs such as Dual Track, has a significant positive impact on teacher performance, strengthening student character, and developing vocational competencies. The implementation of educational technology and interpersonal communication strategies for school principals has also proven to be an important factor in increasing teacher motivation and engagement, as well as supporting the achievement of sustainable educational goals. This study recommends strengthening the role of school principals as visionary, communicative, and adaptive leaders to educational developments in the digital era.